Analysis of Self-Presentation in dr. Richard Lee's Social Media Accounts as a Public Figure in Indonesia: Analisis Presentasi Diri dalam Akun Media Sosial dr. Richard Lee di Akun Media Sosial sebagai Public Figure di Indonesia - Maulidina , Nafridha; Aini, Nur (Procedia of Social Sciences and Humanities, 2025)
This research aims to analyze the self-presentation strategies implemented by Dr. Richard Lee, a public figure in Indonesia, via his social media account. In this research, the author refers to the self-presentation theory put forward by Erving Goffman, which explains how individuals manage the impressions they convey to audiences in various social situations. With a qualitative descriptive approach, data was collected through observation of Dr. Richard Lee, which includes published videos, photos and texts. The research results revealed that Dr. Richard Lee applies a front stage strategy to build his professional image as a beauty doctor and educator, while creating a personal relationship with the audience through content that tends to be informal and humorous.